Effect of Winter and Summer Season on Lipid Peroxidation and Total Seminal Plasma Protein of Tharparkar Bull Semen - Rajoriya, J. S.; Kumar, Sandeep; Shinde, Santhosh; Kumar, Ashok; Perumal, P.; Chauhan, Manisha (International Journal of Bio-resource and Stress Management, 2016)
The present study was undertaken to comparatively study the various particulars in fresh, pre-freeze and post-thaw stage across the season in indigenous breed Tharparkar. A total of 60 ejaculates, 30 each of winter and summer (mass motility ≥3+, initial motility ≥70%) were collected from three bulls (20 from each bull). Part of fresh ejaculate was centrifuged and seminal plasma was used for estimation of TSPP while the sperm pellet was used for the estimation of extent of LPO. Rest of the sample was diluted with Tris-fructose-egg yolk-citrate, equilibrated and frozen by the standard procedure. The total semen volume was significantly (p<0.01) higher in summer (4.45±0.18 ml) as compared to winter season (3.56±0.22 ml). However the levels of total seminal plasma proteins (TSPP) in fresh semen were similar in both winter (10.02±0.66 g dl-1) and summer (9.75±0.19 g dl-1) seasons. TSPP were also found to be negatively correlated with concentration (r=-0.39), mass activity (r=-0.47), initial progressive motility (r=-0.29) and livability of sperm (r=-0.29) in winter season and positively correlated with LPO (r=0.39). Mean pre-freeze and post-thaw motility in winter and summer season did not differ significantly. A significantly (p<0.01) lower values of LPO were estimated in winter (4.26±0.07 n mol 108-1 spermatozoa) than in summer (4.48±0.07 n mol 108-1 spermatozoa) season at post-thaw stage. The levels of LPO in winter and summer were similar at fresh and pre-freeze stages but differed significantly at the post thaw stage suggesting that this parameter may act as an indicator for assessment of damages rendered to spermatozoa by the freeze-thaw cycle. LPO levels were found to be negatively correlated with concentration (r=-0.57), mass activity (r=-0.6), initial progressive motility (r=-0.79) and live per cent (r=-0.79) at fresh stage in both seasons